Participants teach nurses how to facilitate forgiveness through lived experiences with media: A qualitative study - Ann Gentry Recine; Louis Recine; Ann Aschenbrenner; Shawna Helmuth; Megan Jacobson; Summer Peoples; Nick Walther (Wiley, 2023)
Abstract Aims The first aim was to learn what books and other media the study participants would recommend for inspiring people to let go of anger towards themselves or others and have a kinder intention towards themselves or others. The second aim was to learn which media had these effects on participants, and how. The third aim was to compile lists of cited media that can be available to nurses and other healthcare professionals who want to utilize media therapy for the facilitation of forgiveness. Design Phenomenological qualitative. Methods Thematic analysis of semi‐structured interviews with 39 participants. Results A total of 166 diverse media were identified as useful for helping people forgive, which were compiled into tables and categorized into cross‐culturally useful forgiveness process themes. Findings also verified and expanded a previously compiled forgiveness guidance document that summarized the findings of 11 qualitative studies revealing how people forgive.